The Intelligent Leader - Mattone, John (Ascent Audio, 2019)
What is great leadership? What separates the merely competent leaders from those rare individuals who leave a lasting impression on everyone around them? As one of the world's most in-demand CEO coaches and top leadership gurus, John Mattone has worked with some of our brightest business minds-Apple's Steve Jobs, Pepsi's Roger Enrico, and Nielsen's Armando Uriegas-and he's identified the key qualities that, together, make up the mindset of great leadership. In The Intelligent Leader, Mattone lays out an accessible, practical, and compelling path that anyone can take to become the kind of leader that brings enrichment to the lives of others, enjoys a more fulfilling life, and leaves a lasting legacy. Each chapter uses a variety of real-world examples, tools, and assessments to explore one of Mattone's seven dimensions of Intelligent Leadership, including thinking differently, thinking big; having a mindset of duty vs. a mindset of entitlement; leveraging your gifts and addressing your gaps; and having the courage to execute with pride, passion, and precision.